The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.chemrestox.6b00253
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin and Clavulanate Form Chemically and Immunologically Distinct Multiple Haptenic Structures in Patients

Abstract: Amoxicillin-clavulanate (AC) is one of the most common causes of drug induced liver injury (DILI). The association between AC-DILI and HLA alleles and the detection of drug-specific T cells in patients with AC-DILI indicate that the adaptive immune system is involved in the disease pathogenesis. In this study, mass spectrometric methods were employed to characterize the antigen formed by AC in exposed patients and the antigenic determinants that stimulate T cells. Amoxicillin formed penicilloyl adducts with ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
71
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 29 publications
7
71
0
2
Order By: Relevance
“…To gain insight into the nature of the relevant determinants formed, we investigated the protein conjugation process using HSA as a model. We observed that covalent binding of CLV to HSA takes place in vitro and that this modification is concentration‐dependent, consistent with recent studies . The identification of the sites modified by CLV in HSA was carried out only for the conjugate formed at the lowest CLV concentration that allowed detection of protein modification, although still higher than that of the drug in vivo under therapeutic conditions .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…To gain insight into the nature of the relevant determinants formed, we investigated the protein conjugation process using HSA as a model. We observed that covalent binding of CLV to HSA takes place in vitro and that this modification is concentration‐dependent, consistent with recent studies . The identification of the sites modified by CLV in HSA was carried out only for the conjugate formed at the lowest CLV concentration that allowed detection of protein modification, although still higher than that of the drug in vivo under therapeutic conditions .…”
Section: Discussionsupporting
confidence: 89%
“…Compared to penicillins, for which several antigenic determinants have been characterized, CLV reactivity is very complex and degradation pathways after its conjugation to proteins may lead to multiple possible determinants . We have hypothesized the formation of two main antigenic determinants (AD‐I and AD‐II) in conditions similar to those occurring in the clinical practice, based on preliminary reported data and the chemical reactivity of CLV , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, incubation of human serum albumin (HSA) with AX, results in the modification of several lysine residues of which, Lys190 and Lys195 appear to be the most reactive [8]. Interestingly, after oral administration of AX, only modified Lys190 has been found [11,12]. Apart from the chemical reactivity of the antibiotic and the protein residues, little is known about other factors influencing protein haptenation by AX in biological settings.Previous studies with the antibiotic sulfamethoxazole have shown that oxidative stress can potentiate the formation of protein adducts in cells [13].…”
mentioning
confidence: 99%